Correlation of serum omentin-1 level with clinical features and major adverse cardiac and cerebral events in patients undergoing continuous ambulatory peritoneal dialysis. (3rd April 2023) - Yao, Chunmeng; Ou, Juanjuan; Zhou, Liping; Liu, Junlan
Abstract: Omentin-1 shows a critical protective role of cardiovascular events in chronic kidney disease. This study aimed to further assess serum omentin-1 level and its relationship with clinical features and accumulating major adverse cardiac/cerebral events (MACCE) risk in end-stage renal disease patients undergoing continuous ambulatory peritoneal dialysis (CAPD-ESRD). Totally, 290 CAPD-ESRD patients and 50 healthy controls (HCs) were recruited, and their serum omentin-1 levels were measured by enzyme-linked immunosorbent assay. All CAPD-ESRD patients were followed up for 36 months to assess accumulating MACCE rate. Omentin-1 level in CAPD-ESRD patients was lower than that in HCs [median (interquartile range): 229.350 (153.575–355.550) vs. 449.800 (354.125–527.450) pg/mL] ( p  < 0.001). Moreover, omentin-1 level was inversely related to C-reactive protein (CRP) ( p  = 0.028), total cholesterol ( p  = 0.023), and low-density lipoprotein cholesterol ( p  = 0.005), while there was no correlation in omentin-1 level with other clinical features in CAPD-ESRD patients. The accumulating MACCE rate was 4.5%, 13.1%, and 15.5% in the first, second, and third years respectively, and it was lower in CAPD-ESRD patients with high level of omentin-1 than those with low level of omentin-1 ( p  = 0.004). Furthermore, omentin-1 (hazard ratio (HR)=0.422, p  = 0.013) and high-density lipoprotein cholesterol (HR = 0.396, p  = 0.010) were independently associated with reduced accumulating MACCE rate; while age (HR = 3.034, p  = 0.006), peritoneal dialysis duration (HR = 2.741, p  = 0.006), CRP (HR = 2.289, p  = 0.026), serum uric acid (HR = 2.538, p  = 0.008) were independently related to higher accumulating MACCE rate in CAPD-ESRD patients. In conclusion, serum high omentin-1 level is associated with decreased inflammation, lipid levels, and accumulating MACCE risk in CAPD-ESRD patients.